2021
DOI: 10.1002/advs.202101230
|View full text |Cite
|
Sign up to set email alerts
|

IDH Mutation Subgroup Status Associates with Intratumor Heterogeneity and the Tumor Microenvironment in Intrahepatic Cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (ICC) is highly heterogeneous. Here, the authors perform exome sequencing and bulk RNA sequencing on 73 tumor regions from 14 ICC patients to portray the multi-faceted intratumor heterogeneity (ITH) landscape of ICC. The authors show that ITH is highly concordant across genomic, transcriptomic, and immune levels. Comparison of these data to 8 published datasets reveals significantly higher degrees of ITH in ICC than hepatocellular carcinoma. Remarkably, the authors find that hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…We next investigated the oncogenic events associated with the crosstalk ( Xiang et al, 2021 ). For the copy number events, we found 18q11.2 and 19q13.2 were significantly altered in MIT-high group and 12p13.33 and 17q12 were significantly altered in MIT-low group.…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the oncogenic events associated with the crosstalk ( Xiang et al, 2021 ). For the copy number events, we found 18q11.2 and 19q13.2 were significantly altered in MIT-high group and 12p13.33 and 17q12 were significantly altered in MIT-low group.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, regarding immune status, the IDH subgroup (and in parallel high ITH tumours) showed a colder tumour microenvironment (TME) with fewer CD8+ and more neutrophils ( P < .01). These results suggest that single region sequencing could not be enough to evaluate the molecular profile of a tumour 85 …”
Section: New Strategies For Idh Patientsmentioning
confidence: 98%
“…These results suggest that single region sequencing could not be enough to the molecular profile of a tumour. 85…”
Section: Idh-like Tumoursmentioning
confidence: 99%
“…[ 125 ] A report of the multiregional analysis of 14 resected iCCAs using IHC and single cell RNA sequencing also pointed to an association between IDH mutations and lower CD8 + T cell infiltration and lower cytotoxic T cell activity. [ 126 ] Our group found that mIDH iCCAs had reduced CD8 + T cells based on IHC staining of a set of 15 mIDH and 28 IDH WT biopsies and on analysis of immunological signatures from the International Cancer Genome Consortium transcriptomic dataset (110 iCCAs, 15 mIDH1). [ 85 ] Finally, a study of 149 resected iCCA specimens reported two subclasses based on transcription profiles: IDH mutations were enriched in the “proliferation subtype” demonstrating classical oncogenic pathway transcriptional signatures (e.g., MAPK signaling) as compared with the “inflammation subtype,” which was characterized by immune‐related signaling.…”
Section: Introductionmentioning
confidence: 99%